Pembuktian Akta Dibawah Tangan Untuk Digunakan Sebagai Alat Bukti Di Pengadilan - Ayu, Rafida Sartika; Santoso, Aris Prio Agus; Muftiyanto, Taufiq Nur (RIO LAW JURNAL, 2025)
Evidence is an important stage in civil proceedings. At the evidentiary stage, the parties are given the opportunity to show the truth of the legal facts in dispute. There are various types of evidence in the evidentiary stage in civil procedural law, one of which is written/letter evidence. The purpose of this research is to find out the legal proof of private deeds and to find out the legal steps to test the proof of private deeds. The method used in this research is normative, with research specifications being analytical descriptive. The results of the research show that proof of the underhanded deed in civil cases, as long as the underhanded deed is not denied by the parties, the underhanded deed has the same legal force as an authentic deed, whereas if the authenticity of the signature in the underhanded deed is denied of its truth, the underhanded deed should be proven to be true using other evidence and the party submitting the document is required to prove the truth of the signing or contents of the deed. The legal steps to prove using the underhanded deed evidence submitted at the evidentiary stage. In its implementation, the judge considers the evidence presented and considers the historical contents of the underhanded deed.